AN EMPIRICAL STUDY OF CORPORATE GOVERNANCE AND LOAN PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Magembe, Jane M.; Ombuki, Charles; Kiweu, Joséphat M. (International Journal of Economics, Commerce and Management, 2017)
The purpose of this study was to establish the effect of corporate governance on Loan performance of commercial banks in Kenya. The study examined the corporate governance variables namely: Board Structure (BS), Audit Structure (AS) and CEO duality and their effect on Loan performance of commercial banks. Descriptive research design was used in this study and a sample representation consisting of all CEOs of the entire population of 43 commercial banks in Kenya were used as respondents. Primary data was obtained by administering questionnaires to the CEOs whereas secondary data was obtained from the published annual reports covering five years (2010-2014). Data analysis involved Karl Pearsons Correlation Coefficient and Multiple Regression Analysis and used Stata version 13 program. The study found out that BS has a positive relation while AS has a significantly negative relation on the loan performance of the commercial banks. CEO duality also on the other, shows a positive relation to the LNPLs (Linearlized Non- Performing Loans) in that the separation of the CEOs office and that of the chair leads to a decrease of the LNPLs thus resulting to better loan performance. The study also found out that corporate governance factors (BS, AS and CEO) account for 86% of the loan performance of commercial banks. The study therefore recommended that banks should avoid overloading agenda in their committees to enhance their the quality. It further recommend for more efforts to be employed at increasing other corporate governance variables like; board expertise, policy formulation and board tenure as to improve financial performance in Kenyan banks.
Keywords: Corporate Governance; Board Structure; Audit Structure